Crystal structure of shigella flexneri SF173 reveals a dimeric helical bundle conformation - Kim, Ji Hun; Won, Hyung Sik; Yoon, Won Su; Seok, Seung Hyeon; Jung, Bong Jun; Lee, Seu Na; Sim, Dae Won; Seo, Min Duk (Crystals, 2018)
We report the crystal structure and bioinformatic analysis of SF173, a functionally uncharacterized protein from the human enteropathogenic bacteria Shigella flexneri. The structure shows a tightly interlinked dimer formed by adimeric core comprising α2 and α3 helices from both subunits and swapping the N-terminal α1 helix of each monomer. Structural inspection and genomic analysis results suggest that the SF173 might play its putative function by binding to SF172, the partially overlapped upstream product in the operon. As YaeO (an SF172 orthologue) has been identified to be an inhibitor of the bacterial transcription terminator Rho protein, SF173 is suggested to be involved in the regulation of Rho-dependent transcription termination, by inhibiting the Rho protein binding to SF172/YaeO.
Keywords: Helical bundle; SF173; Shigella flexneri; X-ray crystallography